2007
DOI: 10.1074/jbc.m702677200
|View full text |Cite
|
Sign up to set email alerts
|

Juxtacrine Activation of Epidermal Growth Factor (EGF) Receptor by Membrane-anchored Heparin-binding EGF-like Growth Factor Protects Epithelial Cells from Anoikis While Maintaining an Epithelial Phenotype

Abstract: Loss of cell-matrix adhesion is often associated with acute epithelial injury, suggesting that "anoikis" may be an important contributor to cell death. Resistance against anoikis is a key characteristic of transformed cells. When nontransformed epithelia are injured, activation of the epidermal growth factor (EGF) receptor (EGFR) by paracrine/autocrine release of soluble ligands can induce a prosurvival program, but there is generally evidence for concomitant dedifferentiation. The EGFR ligand, heparin-binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 72 publications
2
48
0
Order By: Relevance
“…3 This may occur in communication between purinergic and EGFR signaling, especially in corneal epithelium, where apoptosis is rare. Other researchers have shown that stimulation of kidney epithelial cells with pro-HB-EGF protects cells from anoikis 41 ; in epithelial cells, HB-EGF may play a role in nucleotide-induced ERK1/2 signaling and migration. 18 In addition, when cells that express high levels of EGFR are stimulated with EGF, the enhanced levels of activated EGFR may be accompanied by an accumulation of the receptors within the cell because of a decrease in the rate of receptor degradation.…”
Section: Discussionmentioning
confidence: 99%
“…3 This may occur in communication between purinergic and EGFR signaling, especially in corneal epithelium, where apoptosis is rare. Other researchers have shown that stimulation of kidney epithelial cells with pro-HB-EGF protects cells from anoikis 41 ; in epithelial cells, HB-EGF may play a role in nucleotide-induced ERK1/2 signaling and migration. 18 In addition, when cells that express high levels of EGFR are stimulated with EGF, the enhanced levels of activated EGFR may be accompanied by an accumulation of the receptors within the cell because of a decrease in the rate of receptor degradation.…”
Section: Discussionmentioning
confidence: 99%
“…64 Moreover, EGFR activation by HB-EGF protected kidney cells from apoptosis in a cell-cell or cell-matrix deprived environment, indicating that HB-EGF has cytoprotective effects. 65 In rat unilateral ureteral obstruction, EGF expression was decreased when compared with normal kidneys. Administration of EGF during acute tubular injury and after relief of unilateral ureteral obstruction attenuated tubular damage and accelerated tubular regeneration.…”
Section: Erbb Signaling In Mechanisms Of Renal Repairmentioning
confidence: 99%
“…A number of studies have validated that anoikis can be inhibited despite loss of cellmatrix adhesion when cell-cell adhesion is preserved among various epithelial carcinoma cell lines (16,28,29). Our research model also revealed a multi-cellular spheroid formation in a time-dependent manner.…”
Section: Anoikis Was Induced By the Knockdown Of Cd147 Expression In mentioning
confidence: 54%